Pathogenicity of fusarium oxysporum isolates from Malaysia and F. oxysporuin f. sp. elaeidis from Africa to seedlings of oil palms (Elaeis guineensis) - Ho, Yin Wan; Varghese, George; Taylor, G. S. (Wiley, 1985)
Pathogenicity tests with Fusarium oxysporum isolated form Malaysian oil palm were made with oil palms seedlings raised form Malaysian seed as well s with wilt-susceptible seedlings gown from African seed. Oil palm seedlings grown form Malaysian seed were also inoculated with African isolates of F. oxysporum f. sp. elaeidis and F. oxysporum var. redolens. The experiments were made under normal soil moisture conditions and under water stress. F. oxysporum f. sp. elaeidis isolates form Africa were pathogenic to oil palm seedlings from Malaysian seeds but the Malaysian F oxysporum isolates were non-pathogenic to plams grown from Malaysian seed or the wilt-susceptible palms from African seed. Seedlings from Malaysian seed proved to be highly susceptible to the vascular wilt disease caused by F. oxysporum f. sp. elaeidis as 75–90% of the palms were infected. The susceptibility of the palms from Malaysian seed varied with different African isolates tested. The Yaligimba isolate from Zaire which was found to be F. oxysporum var. redolens was the most virulent. Disease was more severe when oil palm seedlings were subjected to a period of water stress. The incidence of death in the seedlings under stress conditions was 45% as compared with only 15% for palms grown under normal conditions